The 18.3% Silicon Solar Cells with Nano-Structured Surface and Rear Emitter - 张军娜 汪雷 戴准 唐勋 刘友博 杨德仁 (Chinese physics letters, 2017)
A nano-structured surface is formed on the pyramid structure of n-type silicon solar cells by size-controlled silver nano-particle assisted etching. Such a nano-structure creates a front average weighted reflectance of less than 2.5% in the 300-1200nm range due to the broadband reflection suppression. The sodium hydroxide is used to obtain the low-area surface by post-etching the nano-structure, thus the severe carrier recombination associated with the nano-structured surface could be reduced. After emitter forming, screen printing and firing by means of the industrial fabrication protocol, an 18.3%-efficient nano-structured silicon solar cell with rear emitter is fabricated. The process of fabricating the solar cells matches well with industrial manufacture and shows promising prospects.